Pengembangan Media Pembelajaran Wayang Karakter Muslim pada Mata Pelajaran Pendidikan Kewarganegaran di MIN 3 Jombang - Yulia, Nurul Mahruzah; Niswatul Fithriyah, Dewi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The introduction of behavior according to the values of Pancasila must be pursued from an early age, namely at the elementary education level. So that the attitude of caring, cooperation, and respect between fellow human beings can be strongly integrated in students. In addition, the introduction of local culture is also an urgent matter, so that children can love their own culture more. This research is a Research and Development type of research, using the ADDIE development model which has 5 main stages. This research and development involve various experts, namely media experts and learning experts. The data collection used in this study included interviews, observations, questionnaires, and tests, which were specially prepared according to the theories of learning media development and CitizenshipEducation materials for class 1MI. The results of this development indicate that the material validation test is 90%, the design validation is 95%, and the Field Trial is 94.4%. The average pretest and posttest also increased with the pre-test result of 60.4 and the post-test average of 85.6. This shows that the developed media can be said to be valid and can be used in Civic Education learning.